Dissecting the Metabolic Phenotype of the Antihypertensive Effects of Five Uncaria Species on Spontaneously Hypertensive Rats - Feng, Zijin; Hou, Jinjun; Yu, Yang; Wu, Wenyong; Deng, Yanping; Wang, Xia; Zhi, Haijuan; Zhang, Linlin; Wu, Wanying; Guo, De-an (Frontiers in Pharmacology, 2019)
The sourcing of plants from multiple botanical origins is a common phenomenon in traditional Chinese medicines. Uncaria Stem with Hooks (UHs) is approved for using five botanical origins in the Chinese Pharmacopoeia (2015 Edition). All five UHs are commonly used for treating hypertension, even though the plants have different chromatographic fingerprints based on our previous study. However, their hypotensive effects and metabolic phenotypes have not been fully studied. In the present study, spontaneously hypertensive rats (SHRs) were orally administered five aqueous extracts (4 g crude drug/kg) prepared from the different UHs over a six-week period. Systolic blood pressure (SBP) was measured every week and urine was collected after SBP measurement. Untargeted metabonomics was performed using UPLC coupled with a LTQ-Orbitrap mass spectrometer. Bidirectional orthogonal projection to latent structures-discriminant analysis (O2PLS-DA), Student’s t test, and correlation analysis were used for pattern recognition and the selection of significant metabolites. A similar and prolonged reduction of SBP was observed in each of the groups given the five different UHs, while the metabolic profiles were perturbed slightly compared with that of SHR. Further analysis has shown that only a few common, different components were observed within the five groups which showed the similar antihypertensive effect in spite of the distinct metabolic pathways due to their different alkaloid composition. These results help understanding the mechanisms of the phenomenon “different species, same effect” of UHs.